2012
DOI: 10.1038/nature10957
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen-induced human TH17 cells produce IFN-γ or IL-10 and are regulated by IL-1β

Abstract: IL-17-producing CD4+ T helper cells (TH17) have been extensively investigated in mouse models of autoimmunity. However, the requirements for differentiation and the properties of pathogen-induced human TH17 cells remain poorly defined. Using an approach that combines the in vitro priming of naive T cells with the ex vivo analysis of memory T cells, we describe here two types of human TH17 cells with distinct effector function and differentiation requirements. Candida albicans-specific TH17 cells produced IL-17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

63
793
6
16

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 841 publications
(878 citation statements)
references
References 30 publications
63
793
6
16
Order By: Relevance
“…Various T helper cell subsets are involved in host defense, and a tight balance between these populations and the subsequently produced pro-and anti-inflammatory cytokines is essential for immune homeostasis (1,2). A growing body of literature documents that a disruption of this balance can result in chronic inflammation and autoimmunity or increased susceptibility to infections.…”
Section: Inflammation | Gene Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Various T helper cell subsets are involved in host defense, and a tight balance between these populations and the subsequently produced pro-and anti-inflammatory cytokines is essential for immune homeostasis (1,2). A growing body of literature documents that a disruption of this balance can result in chronic inflammation and autoimmunity or increased susceptibility to infections.…”
Section: Inflammation | Gene Regulationmentioning
confidence: 99%
“…Primed CD4 + T cells either migrate to sites of inflammation or persist as circulating effector memory CD4 + T cells. Central memory CD4 + T cells migrate to secondary lymphatic tissues, where they wait for a secondary challenge to exert enhanced immune responses (2,3). Sallusto et al (1999) and others demonstrated that naive, central, and effector memory CD4 + T-cell subsets are defined by the absence or presence of surface markers, including the chemokine receptor CCR7 that reflects tissue-homing capacities to lymph nodes (3).…”
Section: Inflammation | Gene Regulationmentioning
confidence: 99%
“…The use of knockout mouse strains highlighted the role of caspase-1 and ASC in Th17 priming during Candida albicans infection [42 ]. C. albicans-induced IL-1b drives the differentiation of Th17 cells secreting IL-17 alongside with IFN-g [47 ].…”
Section: Inflammasomes and T Cell Responses In Infectionsmentioning
confidence: 99%
“…IL-10 was not only produced by Tr1 cells, but also promoted their differentiation (7). Recently, it also was shown that Staphylococcus aureus priming of naive human T cells generated IL-10-producing Th17 cells (regulatory Th17 cells), potentially as an intrinsic mechanism to suppress excessive inflammation in response to infection (8,9). Studies using in vivo infection with Toxoplasma gondii and Leishmania major revealed that Tbet 1 Th1 cells also secreted IL-10 (10, 11).…”
Section: Il-10: a Paradigm For Counterregulatory Cytokinesmentioning
confidence: 99%